Virtual ID: ID/locator split in a mobile IP environment for mobility, multihoming and location privacy for the next generation wireless networks. (29th September 2010) - So-In, Chakchai; Jain, Raj; Paul, Subharthi; Pan, Jianli
Current networking protocols designed around single interface stationary end-systems clearly fail to represent the present communication context of mobile, multi-interface end-systems. Also, the convergence of wired and wireless technologies into an all-IP (AIP) next generation network will make available multiple diversified contexts that can be leveraged for better fault tolerance, higher availability and improved performance of end-to-end communications. A major reason for the weakness of current protocols may be attributed to the contextual overloading of IP addresses to serve as identifiers as well as locators. Mobile IP (MIP) and its extensions are well-known proposals developed primarily to alleviate the mobility and deployability problems. In this paper, we develop the concept of a virtual identity (ID), as an explicit ID/locator extension of mobile IPv6 and explore its applicability to address the issues of mobility, multihoming, and location privacy in the context of next generation wireless networks.